2019
DOI: 10.1590/1518-8345.2909.3174
|View full text |Cite
|
Sign up to set email alerts
|

Autoconfiança no manejo das intercorrências de saúde na escola: contribuições da simulação in situ

Abstract: Objective to analyze the contributions of the in situ simulation in the self-confidence of early childhood and elementary education teachers regarding the initial management of health complications in school.Method this is a pre-post testing quasi-experimental study. Two pre and post in situ simulation instruments were applied to 76 teachers, namely: visual analogue scale of teachers’ self-confidence in the management of health complications at school, and a questionnaire to assess their knowledge on the subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
28

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 23 publications
(32 reference statements)
2
3
0
28
Order By: Relevance
“…Considerando as situações de engasgo e de RCP em bebês, a prática permite o aprimoramento e a identificação de erros, garantindo um atendimento que minimize risco à vida da vítima (ROSA et al, 2017). Embora esta pesquisa não tenha avaliado a autoconfiança percebida das participantes, evidências da literatura (VAN DER ZWAAN CASTRO, 2018;ZONTA et al, 2019) demonstram que a realização de cursos e capacitações também promovem a autoconfiança dos profissionais para agir diante de uma situação que necessite de primeiros socorros.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Considerando as situações de engasgo e de RCP em bebês, a prática permite o aprimoramento e a identificação de erros, garantindo um atendimento que minimize risco à vida da vítima (ROSA et al, 2017). Embora esta pesquisa não tenha avaliado a autoconfiança percebida das participantes, evidências da literatura (VAN DER ZWAAN CASTRO, 2018;ZONTA et al, 2019) demonstram que a realização de cursos e capacitações também promovem a autoconfiança dos profissionais para agir diante de uma situação que necessite de primeiros socorros.…”
Section: Discussionunclassified
“…Estudo desenvolvido no ano de 2017 junto a instituições de educação infantil e fundamental empregou a estratégia de simulação in situ para promoção da autoconfiança de professores diante de intercorrências no ambiente escolar. O escore de autoconfiança no pré-teste para o item "eu me sinto confiante para reconhecer quando uma criança está engasgando" foi de 4,56, enquanto que no pós-teste foi de 6,93 (ZONTA et al, 2019).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Another study developed in situ with teachers of kindergarten and elementary school I showed that the simulation contributed to increase the self-confidence of these participants to manage health problems in schools, reinforcing the relevance of using this strategy even outside simulation centers (31) .…”
Section: Inter-professional Teaching In Courses Promoted Bymentioning
confidence: 93%